Maternal immune response and placental antibody transfer after COVID-19 vaccination across trimester and platforms - Atyeo, Caroline G.; Shook, Lydia L.; Brigida, Sara; De Guzman, Rose M.; Demidkin, Stepan; Muir, Cordelia; Akinwunmi, Babatunde; Baez, Arantxa Medina; Sheehan, Maegan L.; McSweeney, Erin; Burns, Madeleine D.; Nayak, Ruhi; et al. (Nature communications, 2022)
The availability of three COVID-19 vaccines in the United States provides an unprecedented opportunity to examine how vaccine platforms and timing of vaccination in pregnancy impact maternal and neonatal immunity. Here, we characterize the antibody profile after Ad26.COV2.S, mRNA-1273 or BNT162b2 vaccination in 158 pregnant individuals and evaluate transplacental antibody transfer by profiling maternal and umbilical cord blood in 175 maternal-neonatal dyads. These analyses reveal lower vaccine-induced functions and Fc receptor-binding after Ad26.COV2.S compared to mRNA vaccination and subtle advantages in titer and function with mRNA-1273 versus BN162b2. mRNA vaccines have higher titers and functions against SARS-CoV-2 variants of concern. First and third trimester vaccination results in enhanced maternal antibody-dependent NK-cell activation, cellular and neutrophil phagocytosis, and complement deposition relative to second trimester. Higher transplacental transfer ratios following first and second trimester vaccination may reflect placental compensation for waning maternal titers. These results provide novel insight into the impact of platform and trimester of vaccination on maternal humoral immune response and transplacental antibody transfer. Pregnant individuals infected with SARS-CoV-2 are at high risk of morbidity and mortality, in addition to adverse pregnancy outcomes, yet little is known regarding trimester-specific immunity and maternal protection from COVID-19 vaccine platforms. Authors utilise a systems serology approach to characterise the material antibody response and the transplacental antibody transfer, dependent on vaccine platform and trimester of vaccination.